2020
DOI: 10.2340/00015555-3368
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab Efficacy and Safety in Adolescents with Moderate-to-Severe Atopic Dermatitis: A Case Series

Abstract: Table I. Dupilumab in paediatric patients with atopic dermatitis Study Cork et al. (2) Simpson et al. 1 Treister & Lio (3) Present stydy Number of patients 40 251 8 4 Dosage 2 or 4 mg/kg DUPI 300 mg q4w DUPI 200 mg/ 300 mg q2w DUPI 600 mg and 300 mg q2w Advances in dermatology and venereology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…In adolescents treated with dupilumab, the phase III randomized, placebo‐controlled, clinical trial (R668‐AD‐1526 LIBERTY AD ADOL, NCT03054428) 8 and the phase IIa and subsequent phase III open label extension (R668‐AD‐1412, NCT02407756; R668‐AD‐1434 LIBERTY AD PED‐OLE, NCT02612454) 9 showed significant improvement of AD signs and symptoms, with a good safety profile. To date, only few real‐world data are available on effectiveness and safety of dupilumab in adolescents 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adolescents treated with dupilumab, the phase III randomized, placebo‐controlled, clinical trial (R668‐AD‐1526 LIBERTY AD ADOL, NCT03054428) 8 and the phase IIa and subsequent phase III open label extension (R668‐AD‐1412, NCT02407756; R668‐AD‐1434 LIBERTY AD PED‐OLE, NCT02612454) 9 showed significant improvement of AD signs and symptoms, with a good safety profile. To date, only few real‐world data are available on effectiveness and safety of dupilumab in adolescents 10 …”
Section: Introductionmentioning
confidence: 99%
“…To date, only few real-world data are available on effectiveness and safety of dupilumab in adolescents. 10…”
mentioning
confidence: 99%
“…2 Gene polymorphisms that result in amino acid substitutions could affect the structure of the molecule and, therefore, become susceptible to autoantibody attack. 3 Clinically, this results in generalized or localized skin blistering, such as junctional epidermolysis bullosa 2 or epidermolysis bullosa simplex. 4 Until recently, the pathogenesis of hereditary and acquired autoimmune skin blistering diseases has been thought to be distinct.…”
Section: Col17a1 Gene Polymorphisms Are Frequent In Bullous Pemphigoidmentioning
confidence: 99%
“…Although large clinical trials in adolescents have demonstrated its safety and efficacy, 1,2 few real-life data are still available. 3 Studies carried out required a 4-week washout period for any systemic immunosuppressants prior to starting dupilumab. However, in clinical practice, this procedure is not often performed.…”
mentioning
confidence: 99%
“…It is the first biologic treatment for AD approved by the food and drug administration (FDA) and European Medicines Agency (EMA) in 2017 based on clinical trials that have successfully proven its clinical safety and effectiveness [9][10][11]. Due to a strict patient selection policy in clinical trials, these data are not always reproducible in daily clinical practice, and real-world data may differ in effectiveness and safety [12]. Here, we present data of effectiveness and side effects of Dupilumab treatment in a real-life Austrian patient population.…”
Section: Introductionmentioning
confidence: 99%